Analisis Yuridis Kedudukan Hukum Nota Kesepahaman Dalam Pranata Hukum Kontrak Di Indonesia - Azamta Besnata Mutiara; Arief Suryono (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The lack of regulation regarding the position of a memorandum of understanding often causes disputes between the parties who make it. The position of the memorandum of understanding is very important because it affects the legal consequences. The position can be studied through several aspects, namely based on classical and contemporary contract law theories, the Civil Code, civil law and common law legal systems, and UNIDROIT arrangements. The result of this research is that Indonesia tends to adhere to classical contract law theory by adhering to Article 1320 of the Civil Code. Furthermore, as a civil state (not fully), Indonesia regulates good faith in the nomenclature of legislation, namely Article 1338 (3) and 1965, but has not specifically regulated the good faith of the memorandum of understanding. Indonesia has also ratified UNIDROIT, so that the memorandum of understanding needs to be adjusted to the principles of good faith and fair dealing contained in Article 1.7 of UNIDROIT.